PENERAPAN RESTITUSI TERHADAP ANAK YANG MENJADI KORBAN KEJAHATAN SEKSUAL (Studi Penelitian Di Pengadilan Negeri Bireuen) - Ananda Bagus Prayuda (Nanggroe: Jurnal Pengabdian Cendikia, 2022)
Article 71D paragraph (1) of the Law of the Republic of Indonesia Number 35oof 2014 concerning Amendmentssto Law Number 23 of 2002 concerning Childl Protection states"Every child who becomes a victim as referred to in Article 59 paragraph (2) letter b, letter d, letter f, letter h, letter i, and letter j have the right to submit to the court the right to restitution which is the responsibility of the perpetrator of the crime”. Article 59 paragraph (2) letter J of the law above refers to "child victims of sexual crimes". However, in the Legal Territory of the Bireuen District Court, there is not a single case in the court's decision where the victim received restitution. The purpose of writing this thesis is to explain the factors that the right of restitution is not applied to cases of sexual crimes against children and to explain the obstacles and efforts to overcome in implementing the right of restitution for child victims of sexual crimes. This research was carried out using an empirical juridical approach with a literature and field research approach. Literature research was conducted to obtain theoretical secondary data, while field research was conducted to obtain primary data through interviews with informants and respondents. The results showed that the lack of knowledge possessed by P2TP2A employees, investigators, prosecutors, judges, and victims regarding regulations on restitution was one of the reasons so that the application of restitution could not be carried out properly. The obstacle is that the perpetrators are unable to pay the restitution, let alone to pay the restitution fee, for the cost of daily meals, the perpetrator is not there. So that the application of restitution cannot run properly. Efforts that can be made are conducting socialization, training, and further education regarding restitution. It is recommended to the LPSK to have representatives in the regions so that the fulfillment of the victim's right to receive restitution can be carried out, because LPSK is an institution whose duty is to protect and guarantee the fulfillment of the rights of witnesses and victims.